2017
DOI: 10.1016/j.ejbas.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of blended virgin coconut oil and fish oil on growth performance and resistance toStreptococcus iniaechallenge of Nile tilapia (Oreochromis niloticus)

Abstract: Five isolipidic experimental diets (32% crude protein) were formulated to contain 3% fish oil (FO) and virgin coconut oil (3VCO) as sole lipids or blends of FO + VCO in ratios of 75:25% (0.75VCO), 50:50% (1.5VCO) and 25:75% (2.25VCO). Triplicate groups of O. niloticus were fed one of five diets to apparent satiation, twice daily for 8 weeks. It was observed that fish fed diet 3VCO exhibited the best performance with respect to feed intake (492.1 g), final weight (214.60 g) and weight gain (154.90 g). Significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 58 publications
5
17
1
1
Order By: Relevance
“…niloticus with PO in place could negatively affect the nutritional status of the final product. This is because groups fed 75% PO and 100% PO recorded the least n-3: n-6 ratio and is in agreement to previous study [ 28 ] which reported that feeding O . niloticus with coconut oil reduces n-3: n-6 ratios.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…niloticus with PO in place could negatively affect the nutritional status of the final product. This is because groups fed 75% PO and 100% PO recorded the least n-3: n-6 ratio and is in agreement to previous study [ 28 ] which reported that feeding O . niloticus with coconut oil reduces n-3: n-6 ratios.…”
Section: Discussionsupporting
confidence: 93%
“…iniae —ARS-98-60) was obtained from National Pathogen Collection Center for Aquatic Animals (Shanghai Ocean University). The bacterium was cultured following procedures described previously by [ 28 ]. In order to ascertain the lethal dose, 96 h LD50 was determined by intraperitoneal injection using graded doses of S .…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have used fish oil as a food additive by adding it to yogurt (Zhong et al, 2018), butter (Subroto et al, 2018) and bakery products such as cakes (Santhanam et al, 2015). Fish oil mixed with vegetable oil can enrich omega-3 fatty acids, like virgin coconut oil (Apraku et al, 2017), linseed oil and palm oil (Monge-Ortiz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is also now generally recognized that partial or full substitution of FO is more feasible for freshwater fish than marine species which apparently lack the ability to desaturate and elongate C 18 PUFA and therefore are very prone to n-3 LC-PUFA deficiency (Tocher 2010). Indeed, a review of previous experiments with freshwater species such as Murray cod, Maccullochella peelii peelii (Turchini et al 2011a); pikeperch, Sander lucioperca (L.) (Kowalska et al 2012); snakehead, Channa striatus (Aliyu-Paiko and Hashim 2012); darkbarbel catfish, Pelteobagrus vachelli (Jiang et al 2013); Nile tilapia, Oreochromis niloticus (Peng et al 2015;Apraku et al 2017); gibel carp, Carassius auratus gibelio (Zhou et al 2016); silver catfish, Rhamdia quelen (Lazzari et al 2016); and rainbow trout, Oncorhynchus mykiss (Gause and Trushenski 2013;Yıldız et al 2018); has shown that it is possible to replace FO by single or a mixture of terrestrial oils (both vegetable and animal oils) without compromising growth or feed efficiencies.…”
Section: Introductionmentioning
confidence: 99%